RE chronicle 2001-2003. - Philippines National Electrification Administration (Quezon City National Electrification Administration, 2003)
This CD-ROM contains profiles and statistical data of electronic cooperatives and other utilities in the country. Also included is NEA's organizational structure, board of administrators and executive officials.
Contents: 1. Part I. Introduction -- 2. Part II. Write-ups and tables -- 3. Part III. Graphs -- 4. Part IV. Maps.
Title from introduction PPT file.
Place of publication taken from NEA website.
Keywords: Rural electrification -- Philippines